Menggali Kearifan Lokal: Pendidikan Nilai Dalam Permainan Tradisional Suku Sasak - Muliadi, Erlan; Asyari , Akhmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Traditional games of the Sasak tribe are an integral part of local wisdom and the culture of the Lombok community. However, currently, interest in these traditional games has declined, especially among children. This research aims to unearth local wisdom through the values education embedded in traditional Sasak tribal games. The research method involves introducing traditional games to children through direct play activities, enabling them to understand the meaning and values inherent in each game. Data collection techniques include participatory observation and interviews with traditional players and local community figures. The collected data are analyzed using a qualitative approach, detailing the moral, cultural, and social values found in traditional games. The results show that traditional games of the Sasak tribe encompass values of local wisdom, including team solidarity, precision, and a sense of responsibility. The implications of this research underscore the importance of preserving and integrating traditional games into values education as a means to conserve local culture and shape the character of children by appreciating the noble values of local traditions. This research is expected to make a positive contribution to the preservation of local wisdom and values education amid the ongoing tide of globalization.